Analysis of Microbial Water Contamination, Soil Microbial Community Structure, and Soil Respiration in a Collaborative First-Year Students as Scholars Program (SAS) - Stiemsma, Leah T.; Davis, Stephen D.; Brewster, Jay L. (Frontiers in Microbiology, 2020)
The persistence of college students in STEM majors after their first-year of college is approximately 50%, with underrepresented populations displaying even higher rates of departure. For many undergraduates, their first-year in college is defined by large class sizes, poor access to research faculty, and minimal standing in communities of scholars. Pepperdine University and Whittier College, funded by a National Science Foundation award to Improve Undergraduate Stem Education (NSF IUSE), partnered in the development of first-year classes specifically geared to improve student persistence in STEM and academic success. This Students as Scholars Program (SAS) engaged first-year undergraduates in scholarly efforts during their first semester in college with a careful approach to original research design and mentoring by both faculty and upperclassmen experienced in research. Courses began by introducing hypothesis formulation and experimental design partnered with the scientific focus of each course (ecological, biochemical, microbiological). Students split into research teams, explored the primary literature, designed research projects, and executed experiments over a 6-7 week period, collecting, analyzing, and interpreting data. Microbiology-specific projects included partnerships with local park managers to assess water quality and microbial coliform contamination at specified locations in a coastal watershed. In addition, students explored the impact of soil salinity on microbial community structure. Analysis of these samples included next-generation sequencing and microbiome compositional analysis via collaboration with students from an upper division microbiology course. This cross-course collaboration facilitated additional student mentoring opportunities between upperclassmen and first-year students. This approach provided first-year students an introduction to the analysis of complex data sets using bioinformatics and statistically reliable gas-exchange replicates. Assessment of the impact of this program revealed students to view the research as challenging, but confidence building as they take their first steps as biology majors. In addition, the direct mentorship of first-year students by upperclassmen and faculty was viewed positively by students. Ongoing assessments have revealed SAS participants to display a 15% increased persistence rate in STEM fields when compared to non-SAS biology majors.